Pelatihan Kewajiban Perpajakan Baik Perhitungan dan Pelaporan Bagi Aparat Desa Kerinjing - Yusnaini; Sri Maryati (Sriwijaya Accounting Community Services, 2022)
The potential for fisheries in Kerinjing village are fishermen who catch wild rice fields and some cultivate freshwater fish, there are still many skilled human resources but cannot use their expertise in general because they are not supported by adequate skills education and a lot of job competition. Demands for transparency and accountability in management Village government finances require villages to clean up and prepare themselves through various activities, including socialization and technical guidance on financial management. The implementation of this service is in the form of training to facilitate the implementation of village government finances, one of which is regarding taxation. The role of village officials in Kerinjing Village, Tanjung Raja Ogan Ilir sub-district with regard to taxation is very large. In the implementation of this service, there are several questions related to tax obligations that must be carried out by the village government. Thus, in the implementation of this service, they actively discuss relating to calculating taxation, not only Income Tax (PPh) but also Value Added Tax (VAT) and stamp duty